Uncovering mutation-specific morphogenic phenotypes and paracrine-mediated vessel dysfunction in a biomimetic vascularized mammary duct platform - Matthew L. Kutys (Nature Portfolio, 2020)
In vitro models of the human mammary gland have struggled to mimic the 3D morphogenic processes that occur in vivo. Here the authors develop a 3D microfluidic platform of a vascularized human mammary duct that simulates diverse morphogenic transitions and paracrine crosstalk.